POTENSI TANAMAN RAMI (Boehmeria nivea) UNTUK FITOREMEDIASI TANAH TERCEMAR TEMBAGA - Nina Dwi Lestari; Naufal Rizka Pratama (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2020)
One of the heavy metals that most contaminates the environment and soil is copper (Cu) that mostly comes from the activities of electroplating industries. This study aimed to identify the ability of Boehmeria nivea in absorbing Cu absorption from planting medium containing Cu. The Boehmeria nivea plant was grown on soil contaminated with six CuSO4 concentration levels, i.e.Â 0 ppm Cu (P0), 10 ppm Cu (P1), 20 ppm Cu (P2), 30 ppm Cu (P3), 40 ppm Cu (P4), and 50 ppm Cu (P5). The results showed that Boehmeria nivea plant could absorb Cu and survive in the Cu levels of 25 â€“ 125 ppm in the soil. The Bioremediation Index indicated that Boehmeria nivea could reduce copper in the soil up to more than 50%. The mechanism of phytoremediation was categorized into phytostabilization, since the result of all treatments showed the value of translocation factor (TF) of less than 1. The presence of Cu in the soil affected plant height and leaf number of the plant Boehmeria nivea. However, on the actual condition, Boehmeria nivea did not show any symptom of Cu toxicity